The creative power of affective discourse. Recapitulating deleuze - Kłos-Czerwińska, Paulina (Hybris, 2020)
In the following article an attempt is made to draw the reader’s attention to the problem of affective and emotional poverty which has resulted from the systematic degradation of everyday experience in contemporary times. The analysis of this problem is based on the writings of different continental philosophers, especially Gilles Deleuze, but also others, like Michel Foucault or Maurice Blanchot. It is suggested that the solution to this problem may lie in the power of creation, and I have tried to offer the reader some techniques or methods which, if undertaken, may develop creativity and release its power. However, the best repertoire of such techniques is to be found in the writings of the above mentioned researchers, so the reader is directed to the original sources.